Advancing healthcare through data: the BETTER project's vision for distributed analytics - Bregonzio, Matteo; Bernasconi, Anna; Pinoli, Pietro (Frontiers in Medicine, 2024)
Introduction Data-driven medicine is essential for enhancing the accessibility and quality of the healthcare system. The availability of data plays a crucial role in achieving this goal. Methods We propose implementing a robust data infrastructure of FAIRification and data fusion for clinical, genomic, and imaging data. This will be embedded within the framework of a distributed analytics platform for healthcare data analysis, utilizing the Personal Health Train paradigm. Results This infrastructure will ensure the findability, accessibility, interoperability, and reusability of data, metadata, and results among multiple medical centers participating in the BETTER Horizon Europe project. The project focuses on studying rare diseases, such as intellectual disability and inherited retinal dystrophies. Conclusion The anticipated impacts will benefit a wide range of healthcare practitioners and potentially influence health policymakers.